Nivel de aceptación y rentabilidad de la instalación de un parque de diversiones - Distrito de Trujilo. - Alcántara García, Fiorella Paola (2011)
This thesis, entitled “Level of Acceptance and Performance of Installation of Amusement Park– Trujillo District" has as main objective to determine the feasibility of installing an amusement park in the city of Trujillo. Since this is one of the cities of Peru with higher economic growth in recent years and has no deals of this kind, the brand of service called MAGIC PARK. MAGIC PARK had an innovative offer because it incorporates two types of attractions that are innovative rides and adventure, games for providing fun alternatives to adolescents and young people of the city. This offer is sustained after analysis sector amusement park, to direct, indirect and surrogate, competition an estimated of objective demand projection as well as market research. For the study of the consumer a rigorous research work carried out at several levels: review of secondary sources, direct observation and application of surveys. This analysis determined that 96% of respondents are not satisfied with the current offer of amusement parks in the city, represents a huge market to meet. Main assist them factors are the quality of care for the client, security, location of the local and the variety of games. As we also find that 96 per cent of respondents would be willing to attend a new amusement park, which suggests that there, is a high probability of success for the development of this project. Functional strategies have been developed both for the service, price, promotion, advertising, infrastructure and human resources, depending on the attributes of value for customers. The project investment comprises intangible fixed assets and working capital needed for operational management. With this investment of S/. 182,225.81. MAGIC PARK location is strategically within a residential and commercial growth area very close to one of the largest shopping centre’s of Trujillo is the Plaza Adventure Mall and a few meters to the Av. traffic and busy city Av. Mansiche and Pablo Casal. The cash flow expected scenario, projected allows us to estimate revenue during the first five years make feasible project, generating a VANE and positive VANF of S/. 347,903.37, S/. 527,415.96 Respectively. As well as a pull of 94% and TIRF 67%, higher than the discount rate of 16% and 20% respectively. Therefore the project will be feasible and viable for the period analyzed, thus constituting a great investment opportunity and put our city along major cities of the country.